Persepsi Masyarakat terhadap Kerusakan Lingkungan Akibat Penambangan Timah di Kecamatan Koba, Kabupaten Bangka Tengah: English - Ferianda, Agung (STISIPOL Pahlawan 12 Press, 2020)
Bangka island is the biggest Tin Mining centre at Indonesia, bt this mining activity effect to environment damage. Because of that, this research head for study the society to environment damage as consequence of Tin mining activity. Research method that use is survey. Respondent in this research are family head at Nibung village. Berok Village and Simpang Perlang village. The sum of respondent is 90 family heads. Variable that use in this research are dependent variable and independent variable. Dependent variable that is perception and independent variable are education, knowledge, occupation, income, sum of consist of qualitative descriptive analysis and quantitative analysis with helping of SPSS Program. In entire whole society perception about environment damage because of tin mining: 42 % belong to low perception category, 47 % belong to medium perception category, and 11 % belong to high category. Factor that most effecting to society perception is knowledge factor.